Un bref aperçu de l’histoire culturelle du concept d’activité - Yves Schwartz (Activités)
To what extent is there thought and what thought is there under the current use of a peculiar word? Such a question seems to me crucial for a word like “Activity”, which is omnipresent in ordinary language, but whose “thought content” is quite problematic. We speak here of “Activity”, not of “Action”. That survey on the term “activity” is of a prominent importance as far as this Journal mainly concerns ergonomists, some of them having a basic use of this concept.